International percutaneous coronary intervention complication survey. Issue 6 (29th March 2022) - Simsek, Bahadir; Kostantinis, Spyridon; Karacsonyi, Judit; Hall, Allison; Rangan, Bavana V.; Croce, Kevin J.; Azzalini, Lorenzo; McEntegart, Margaret; Shishehbor, Mehdi; Egred, Mohaned; Mastrodemos, Olga C.; Sorajja, Paul; et al.
Abstract: Objectives: To investigate the perceptions of interventional cardiologists (IC) regarding the frequency, impact, and management strategies of percutaneous coronary intervention (PCI) complications. Background: The perceptions and management strategies of ICs of PCI complications have received limited study. Methods: Online survey on PCI complications: 46 questions were distributed via email lists and Twitter to ICs. Results: Of 11, 663 contacts, 821 responded (7% response rate): 60% were from the United States and the median age was 46–50 years. Annual PCI case numbers were <100 (26%), 100–199 (37%), 200–299 (21%), and ≥300 (16%); 42% do not perform structural interventions, others reported performing <40 (30%), or >100 (11%) structural cases annually. On a scale of 0–10, participating ICs were highly concerned about potential complications with a median score of 7.2 (interquartile range: 5.0–8.7). The most feared complication was death (39%), followed by coronary perforation (26%) and stroke (9%). Covered stents were never deployed by 21%, and 32% deployed at least one during the past year; 79% have never used fat to seal perforations; 64% have never used coils for perforations. Complications were attributed to higher patient/angiographic complexity by 68% and seen as opportunities for improvement by 70%; 97% of participants were interested in learning more about the management of PCI complications. The most useful learning methods were meetings (66%), webinars (48%), YouTube (32%), and Twitter (29%). Conclusion: ICs who participated in the survey are highly concerned about complications. Following complication management algorithms and having access to more experienced operators might alleviate stress and optimize patient outcomes.